Working ethically with gatekeeper and participants: a reflection of an ethnographic inquiry of homestay tourism learning - Kanel, Chet Nath; Bhattarai, Prakash C.; Gnawali, Laxman (Journal of Management and Development Studies, 2023)
A gatekeeper's role in an ethnographic study has hardly been explored. Considering this, this article presents an ethnographic study of Nepali homestays’ learning in which a gatekeeper was used as an intermediary to enter the research site and have access to the research participants. The key steps and processes we adopted while selecting and working with the gatekeeper have been explained along with our reflections on the role and ethics balancing strategies applied during the study. In this reflective article, we have interpreted and conclusively asserted that the eight words ended with 'ty'— intentionality, neutrality, conformity, familiarity, mutuality, reciprocity, anonymity, and sustainability— play significant roles in balancing and ethically working with the gatekeeper and the research participants.